Response of the green alga Oophila sp., a salamander endosymbiont, to a PSII‐inhibitor under laboratory conditions. (30th June 2014) - Baxter, Leilan; Brain, Richard; Rodriguez‐Gil, Jose Luis; Hosmer, Alan; Solomon, Keith; Hanson, Mark
Abstract In a rare example of autotroph‐vertebrate endosymbiosis, eggs of the yellow‐spotted salamander (Ambystoma maculatum) are colonized by a green alga (Oophila sp.) that significantly enhances salamander development. Previous studies have demonstrated the potential for impacts to the salamander embryo when growth of the algae is impaired by exposure to herbicides. To further investigate this relationship, the authors characterized the response of the symbiotic algae (Oophila sp.) alone to the photosystem II (PSII) inhibitor atrazine under controlled laboratory conditions. After extraction of the alga from A. maculatum eggs and optimization of culturing conditions, 4 toxicity assays (96 h each) were conducted. Recovery of the algal population was also assessed after a further 96 h in untreated media. Average median effective concentration (EC50) values of 123 µg L−1 (PSII yield), 169 µg L−1 (optical density), and 299 µg L−1 (growth rate) were obtained after the 96‐h exposure. Full recovery of exposed algal populations after 96 h in untreated media was observed for all endpoints, except for optical density at the greatest concentration tested (300 µg L−1). Our results show that, under laboratory conditions, Oophila sp. is generally less sensitive to atrazine than standard test species. Although conditions of growth in standard toxicity tests are not identical to those in the natural environment, these results provide an understanding of the tolerance of this alga to PSII inhibitors as compared with other species. Environ Toxicol Chem 2014;33:1858–1864. © 2014 SETAC